Health-related quality of life in older adults: Effects of hearing loss and common chronic conditions - Simpson, Annie N. (Healthy Aging Res, 2015)
BACKGROUND: Recent findings on hearing loss (HL) and healthy aging have highlighted important clinical and policy implications concerning quality of life in older adults. Our objective was to explore the impact of HL on quality of life in older Americans, independent of survival, using the 2000 Medical Expenditure Panel Survey (MEPS) and 2010 Census data. METHODS: A retrospective cohort of 2,567 subjects aged 60–90 in the MEPS who provided information on self-reported HL, health-related quality of life and chronic conditions. The EQ-5D visual analog scale (VAS) transformation was used to estimate marginal utility decrements for 5-year age categories and conditions, including HL, hypertension, diabetes, angina, joint pain, asthma, emphysema, or blindness. The modeled decrements were applied to the 2010 US census population to estimate annual quality-adjusted life years (QALYs) lost. RESULTS: Of the respondents, 15.4% had mild HL and 1.1% had moderate/severe hearing loss. Other conditions (utility decrement) included: joint pain 53% (.0643), hypertension 47.2% (.0292), diabetes 15.6% (.0577), angina 9.8% (.0352), asthma 7.9% (.0288), emphysema 4.5% (.1186), blindness 0.8% (.0836), and average age 71.0 with decrements .0033 per year. The decrement from hearing loss ranked 4th at 174,689 in the US population. CONCLUSIONS: The substantial impact of hearing loss on healthy aging may not be obvious when quality of life decrements include survival or when diluted with younger populations. Careful consideration of clinical interventions for age-related HL is warranted and further research is needed on the effect of HL on quality of life in otherwise healthy older adults.